Psychological Attention to abused women: a proposal - Huertas Rosales, Rosa Elena (2003)
A Model of Psychological Attention to the battered woman acquires knowledge. Model designed and practiced by more than twelve years in an Infantile Maternal Center of the Ministry of Health, the city of Lima. Gestalt is sustained in the psychotherapy developed by Perls and takes the contributions from the Psychology of the Health and the Communitarian Health that raise the necessity to make primary attention (the WHO, 1978). From a work in multidisciplinary equipment, interinstitutional and in networks it makes high-priority internalize the necessity to coordinate and to work in equipment with the active participation of the community reason why he is basic to construct a integrativo conceptual frame enabling to Promoters for the prevention of the intra family Violence from the organized groups. Similarly it considers that the intervention must consider so much to the «victim» Iike the «aggressor». As far as the therapeutic intervention, this can be individual or group, and through pairs.